Іронія долі чекіста Михайла Ленчика - Бажан, О.; Золотарьов, В. (Краєзнавство, 2018)
У статті на основі наявних архівних документів автори прагнуть відтворити невідомі факти з
біографії та подробиці загибелі начальника особового відділу ГУДБ НКВС 58-ї стрілецької дивізії РСЧА
і Черкаського районного відділу НКВС Михайла Ленчика. In this article, based on available archival documents, the authors seek to recreate unknown facts from
the biography and details of the death of the head of the personal department of the GGB of the NKVD of the
58th Rifle Division of the Red Army and the Cherkassky district department of the NKVD, Mikhail Lenchyk.
The death of the head of the Cherkasy district department of the NKVD Mikhail Fedorovich Lenchyk on May
25, 1937, on a steamship under the name of Stalin, under extremely mysterious circumstances, still excite the
imagination of the researchers of the history of VUCHK-GPU-NKVD-KGB and local lore. Due to the lack of
information, there are various assumptions about the death of a respectable employee of the state security organs
of the Ukrainian SSR. According to one version of the checkbook MF Lench chose a peculiar way of
suicide (thrown overboard a steamer near the city of Kanev) as he was afraid of a future arrest or did not want
to take responsibility for the mass political repression planned for the summer of 1937 in connection with the
preventive social cleansing of the «fifth column». Some believe that the death of M. Lenchyk is the result of a
special operation of the security forces or the revenge of someone from the immediate environment. Judging
by the available archival documents, M. Lenchyk's death was qualified as an accident, not a suicide, which
made it possible to appoint the widow Lenchik Anna Yevstafievna to the Pension Fund of the NKVD.